Pengalaman Wartawan Mengenai Jurnalisme Bencana - Huzaima, Salsa; kusnawan, aep; Tresnawaty, Betty (Annaba: Jurnal Ilmu Jurnalistik, 2021)
The purpose of this study was to find out the experience of broadcast journalists in finding disaster news in disaster news, reporting on disasters and covering natural disasters. By using the phenomenological theory put forward by Alfred Schutz, this study focuses on understanding events with human experience. The research methodology used in this research is descriptive, which aims to clearly reveal the facts, circumstances and events that occurred. The findings conclude that PRFM radio journalists obtain disaster information through community reports, natural disaster agencies and freelance journalists. Can the experience of PRFM Radio journalists when reporting explain the principles of disaster journalism and present natural disaster events according to journalistic ethics.